Tools and Algorithms for the Construction and Analysis of Systems: 24th International Conference, TACAS 2018, Held as Part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2018, Thessaloniki, Greece, April 14-20, 2018, Proceedings, Part I - Dirk Beyer (Theoretical Computer Science and General Issues, 2018)
The LNCS 10805 and 10806 proceedings set constitutes the proceedings of the 24th International Conference on Tools and Algorithms for the Construction and Analysis of Systems, TACAS 2018, which took place in Thessaloniki, Greece, in April 2018, held as part of the European Joint Conference on Theory and Practice of Software, ETAPS 2018. The total of 43 full and 11 short papers presented in these volumes was carefully reviewed and selected from 154submissions. The papers are organized in topical sections as follows: Part I: theorem proving; SAT and SMT I; deductive verification; software verification and optimization; model checking; and machine learning. Part II: concurrent and distributed systems; SAT and SMT II; security and reactive systems; static and dynamic program analysis; hybrid and stochastic systems; temporal logic and mu-calculus; 7th Competition on Software Verification - SV-COMP.